Combinatorial Mathematical Tasks in the Education in Mathematics for Grades 1.- 4. - Temnikova, Maria (European Scientific Journal, ESJ, 2018)
The choice of strategies and their correct combination over the course of training of the students to solve tasks from the area of combinatorics for composing combinatorial compounds from permutation type is one of the important factors for performance of efficient education in mathematics during the classes for extended and additional training in the Primary school. Object of the study is the influence of the applied strategies on the process of acquiring of knowledge, development of skills and competencies in the students for solving tasks from the area of combinatorics in the education in mathematics during the classes for optional education in Grades 1. – 4. The research work was performed in qualitative and quantitative aspects. The following methods were applied: experiment, observation, test, analysis of the content, mathematical-statistical method for data processing. As a result of the study it was found out that due to the applied methodology system of work where different strategies were combined, the competences and competencies for solving tasks from the area of combinatorics were developed in the students from Grades 1.- 4.